Equipment condition monitoring system of grounded aircraft propeller engine: a prototype semi-manual system / Mohd Harridon Mohd Suffian - Mohd Suffian, Mohd Harridon (2006)
The paper outlines the comprehensive and concise doctrines of the prototype of Equipment Condition Monitoring System (ECMS) of a grounded propeller engine of an aircraft. The intended engine is used by students of aviations in lieu with the modules of subjects offered at Universiti Kuala Lumpur Malaysian Institute of Aviation Technology. The condition of the engine, thus, should be at its zenith without constant breakdown or malfunction. The research group of this project projected a procreation of a prototype of ECMS to monitor this particular engine with the purpose of reducing the frequency of corrective maintenance. Corrective maintenance ushers the engine unusable during the tenure of the maintenance process, hence, accommodation of lectures is not parlayed. The paper discerns methods, postulations, axioms, and peripherals of the ECMS and the benefits of actuating this system.